Penerapan Evaluasi Pembelajaran PAI dan Bahasa Arab dengan Tes Tertulis melalui Media Scola Digital Learning Manajemen System (LMS) di SMA Muhammadiyah Al-Kautsar PK Kartasura - Regita, Rahma; Al-Husein, Muhammad Hafidz; Alam, Muhammad Nafis; Inayati, Nurul Latifatul (Lembaga Yasin AlSys, 2024)
The purpose of this study is to determine the process of using the media learning management system (LMS) as a digital-based test in the process of evaluating Islamic Religious Education and Arabic learning at SMA Muhammadiyah Al-Kautsar PK Kartasura. The rapid development of technology, especially in the field of education, teachers are required to be able to innovate, such as by utilizing technology as a means of learning media and as a learning evaluation tool. Learning management system (LMS)-based test media is one of the web-based learning media or applications used as an online-based evaluation process tool that makes it easier for teachers to increase student interest in taking test activities as an evaluation of learning. Learning evaluation by utilizing the use of learning management system (LMS)-based test media is an alternative way that can be used by teachers to see the learning that has been implemented. This research applies qualitative research with the type of case study research, the source of data in this study consists of one resource person, namely PAI and Arabic teachers in schools. The research methods used in this study were interviews and observations. Data analysis by data reduction, data presentation, and conclusions. For data analysis, researchers apply the triangulation method by checking again. The results of this study prove that, SMA Muhammadiyah Al-Kautsar PK Kartasura has used learning management system (LMS)-based test media as an evaluation process tool in learning evaluation. The use of this media still experiences some obstacles in its use. The use of this test media helps facilitate and become an attraction for students in the learning evaluation process activities.